Hubungan antara Karakteristik Responden dan Sikap Kerja Duduk dengan Keluhan Nyeri Punggung Bawah (Low Back Pain) Pada Pekerja Batik Tulis (The Relationship Among Respondent Characteristic and Awkward Posture with Low Back Pain in Batik Workers) - Amalia Riza Umami; Ragil Ismi Hartanti; Anita Dewi P Sujoso (Pustaka Kesehatan, 2014)
The batik worker is one of the occupational working with risk of low back pain. Low back pain is one of clinical syndrome which marked by pain as the main symptom or the pain in low back area. This research aim was to analyze the relationship among respondent characteristic and awkward posture with low back pain in batik workers at batik industry in Sumberpakem, Sumberjambe sub-district with cross sectional design. This research technique analyze use Cramer Coefficient C statistic test with α= 0,05. The results of this research showed that there are significant relations among age (0,031<0,05), length of working (0,00<0,05), nutritional status(0,03<0,05) and also awkward posture (0,001<0,05) with low back pain. Then not significant relationhip between sport habitual (0,201>0,05)with low back pain. Keywords: Respondent Characteristic, Low back pain, Batik workers, Awkward posture